‘Healthier Chinese spine’: an update of osteoporotic fractures in men (MrOS) and in women (MsOS) Hong Kong spine radiograph studies - Wáng, Yì Xiáng J.; Deng, Min; Griffith, James F.; Kwok, Anthony W. L.; Leung, Jason C. S.; Lam, Patti M. S.; Yu, Blanche Wai Man; Leung, Ping Chung; Kwok, Timothy C. Y. (Quantitative imaging in medicine and surgery, 2022)
For the MrOS (Hong Kong) and MsOS (Hong Kong) baseline (BL) studies, community-dwelling 2,000 Chinese men (mean age: 72.3 years) and 2,000 Chinese women (mean age: 72.5 years) were recruited from 2001 to 2003. These two studies have spanned two decades till now. This review summarizes our spine radiograph results. Senile and post-menopausal osteoporosis were associated with intervertebral disc volume reduction; and in women, menopause accelerates disc degeneration. Elderly women's osteoporotic vertebral fracture (OVF) prevalence was double of that of elderly men. For year-4 follow-up (FU), male participants with BL OVF had little increased risk for further OVF. In our study comparing OVF rates in age-matched Hong Kong Chinese women and Italian Caucasian women (mean age: 74.1 years), endplate and/or cortex fracture (ECF) prevalence was 26% for Chinese and 47% for Italian. OVF with ≥40% vertebral height loss was recorded among 9.5% of the Chinese subjects while among 26% of the Italian subjects. OVFs in Italian subjects were more likely to be multiple and generally severer. Clinical spine fractures were recorded 133 cases/100,000 person-years in MrOS (Hong Kong) participants and 273 cases/100,000 person-years in MsOS (Hong Kong) participants. Literature review suggests the clinical vertebral fracture rates among elderly Hong Kong Chinese subjects are approximately half of those of American, Australian, and Canadian subjects. Data synthesis suggests elderly Caucasians have a higher degenerative spondylolisthesis prevalence, being approximately 70% higher than that of elderly Hong Kong Chinese. Literature review of other authors' publications shows, compared with Caucasians, Chinese have a much lower incident rate of back pain. We conclude that elderly Chinese have a generally healthier spine relative to elderly Caucasians.